ARID1A, a factor that promotes formation of SWI/SNF-mediated chromatin remodeling, is a tumor suppressor in gynecologic cancers - Guan, Bin (2011)
ARID1A (BAF250A) promotes the formation of SWI/SNF chromatin remodeling complexes containing BRG1 or BRM. ARID1A has emerged as a candidate tumor suppressor based on its frequent mutations in ovarian clear cell and endometrioid cancers and in uterine endometrioid carcinomas. Here we report that restoring wild-type ARID1A expression in ovarian cancer cells that harbor ARID1A mutations is sufficient to suppress cell proliferation and tumor growth in mice, whereas RNAi-mediated silencing of ARID1A in non-transformed epithelial cells is sufficient to enhance cellular proliferation and tumorigenicity. Gene expression analysis identified several downstream targets of ARID1A including CDKN1A and SMAD3, which are well known p53 target genes. In support of the likelihood that p53 mediates the effects of ARID1A on these genes, we demonstrated that p53 was required and sufficient for their regulation by ARID1A. Further, we showed that CDKN1A (encoding p21) acted in part to mediate growth suppression by ARID1A. Lastly, we obtained evidence that the ARID1A/BRG1 complex interacts directly with p53 and that mutations in the ARID1A and TP53 genes were mutually exclusive in tumor specimens. Our results provide functional evidence in support of the hypothesis that ARID1A is a bona fide tumor suppressor that collaborates with p53 to regulate CDKN1A and SMAD3 transcription and tumor growth in gynecological cancers.